Atta’zīz Al-Lafdzī wa Ghair Al-Lafdzī fī Ta’lim Al-Lughah Al-‘Arabiýah lil-Makfūfīn: Verbal and Non-Verbal Reinforcement in Arabic Language Learning for Visual Disabilities - M. Sobir Kubbaro; Rahil Ayu Na Ziihah; Agung Setiyawan (Jurusan Pendidikan Bahasa Arab UIN Sunan Kalijaga, 2023)
This study aims to analyze the forms of verbal and non-verbal reinforcement by Arabic teachers at Mts.LB Yaketunis Yogyakarta for students with visual disabilities in the process of learning Arabic. The research is based on the complex problems of learning Arabic for students with visual disabilities, which come from external students such as the lack of accessible learning facilities and infrastructure for students with visual disabilities. This qualitative research model is a case study pattern analysis, where data was obtained from interviews with Arabic teachers, field observations as well as questionnaires. The research results show that the forms of verbal reinforcement given by the teacher are directive utterances, commissive utterances, interrogative utterances, and expressive utterances. While the non-verbal include gestural movements and haptic movements. With this research, it is hoped that LB school teachers can pay attention to verbal and non-verbal reinforcement, especially in language learning. Keywords: Verbal Reinforcement, Non-Verbal Reinforcement, Learning Arabic, Blind People ملخص تهدف هذه الدراسة إلى تحليل أشكال التعزيز اللفظي وغير اللفظي من قبل معلمي اللغة العربية في Mts.LB Yaketunis Yogyakarta للطلاب ذوي الإعاقات البصرية في عملية تعلم اللغة العربية. يعتمد البحث على المشكلات المعقدة لتعلم اللغة العربية للطلاب ذوي الإعاقات البصرية ، والتي تأتي من طلاب خارجيين مثل عدم وجود مرافق تعليمية سهلة الوصول وبنية تحتية للطلاب ذوي الإعاقات البصرية. نموذج البحث النوعي هذا هو تحليل نمط دراسة الحالة، حيث تم الحصول على البيانات من المقابلات مع معلمي اللغة العربية ، والملاحظات الميدانية وكذلك الاستبيانات. وأظهرت نتائج البحث أن أشكال التعزيز اللفظي التي يقدمها المعلم هي الكلام التوجيهي، والألفاظ التبادلية، والألفاظ الاستفهام، والألفاظ التعبيرية. بينما تشمل الحركات غير اللفظية الحركات الإيمائية والحركات اللمسية. من خلال هذا البحث ، من المأمول أن يتمكن مدرسو مدرسة الخاصة من الانتباه إلى التعزيز اللفظي وغير اللفظي ، خاصة في تعلم اللغة. الكلمات الرئيسية: التعزيز اللفظي، التعزيز غير اللفظي ، تعلم اللغة العربية ، الأعمى